IDENTIFYING UNHEALTHY HOUSES IN KERINCI DISTRICT, INDONESIA - Yudha Gusti Wibowo; Bimasatyaji Surya Ramadhan; Ummi Kalsum (Universitas Airlangga, 2020)
Background: Healthy houses in developing countries are a critical factor in human health, as the increase in population is not balanced by improvements in local community welfare. This has negative impacts on the environment and human health. Purpose: The aim of this study was to identify unhealthy houses in Kerinci, Indonesia. Method: This research used a descriptive cross-sectional approach. A survey of 122 houses was conducted to determine the characteristics of houses in Kerinci District, Jambi Province, Indonesia. Stratified random sampling was used to obtain representative healthy house data, by using four repetitions on each single question to minimize errors. Results: The results showed that 90% of respondents had a high occupant density. A high number of diseases were already experienced by residents in the area. These diseases were an indication that the area could be classified as unhealthy and included diarrhea (20%), acute respiratory infections (ARI; 13%), malaria (10%), skin diseases (15%), and other diseases (29%). Only 12% of the total respondents reported having no diseases. Conclusion: In the Kerinci District, 98% of houses were classified as unhealthy and as having potentially negative impacts on the health of residents. We recommend the government establish regulations to improve the health of houses and increase economic growth in Kerinci District, Indonesia.